A Cultura Corporal na Educação Infantil: uma análise da Base Nacional Comum Curricular e suas implicações para o trabalho docente: Body Culture in Early Childhood Education: an analysis of the National Curricular Common Core and its implications for teaching work (Revista Cocar, 2021)
Objetiva apresentar uma análise do trato da Cultura Corporal na Educação Infantil a partir dos princípios e concepções da Base Nacional Comum Curricular (BNCC) e apontar algumas implicações para o trabalho docente. Por meio de interpretações críticas e do acúmulo dos campos teórico e empírico, é possível afirmar que o teor curricular perscrutado, em interface da Educação Física, delega reduzida notoriedade ao trato dos elementos da Cultura Corporal desde a tenra infância. Este dado pode refletir no empobrecimento das práticas pedagógicas ao não garantir o ensino de uma parcela crucial da cultura às crianças. Conclui-se que o professor necessita tecer suas interpretações frente à BNCC, reafirmando seu papel como crítico-intelectual no desenvolvimento de ações político-pedagógicas que coadunem com um projeto educativo de formação e desenvolvimento humano.Palavras-chave: Cultura Corporal; Educação Infantil; Base Nacional Comum Curricular; Educação Física. AbstractIt aims to present an analysis about the Body Culture in Early Childhood Education based on the principles and concepts of the National Curricular Common Core (BNCC) and to point out some implications to the teaching work. Through the critical document interpretations and the theoretical background and empirical fields, it is possible to affirm that the curricular content examined, in interface with Physical Education, point out reduced notoriety to the elements of Culture Corporal since early childhood. This data reflects the impoverishment of pedagogical practices by not guaranteeing the crucial part of human culture on the process of development and learning of children at the beginning of Education. Teacher needs to weave his interpretations and analyzes before the BNCC, reaffirming his role as an intellectual-critic in the development of political-pedagogical practices that are consistent with an educational project of human formation.Keywords: Body Culture; Early Childhood Education; National Curricular Common Core; Physical Education.